7th FEB International Scientific Conference: Strengthening Resilience by Sustainable Economy and Business – Towards the SDGs (University of Maribor Press, 2023)
Sustainability is an increasingly important mechanism for the resilience and competitiveness of economies and businesses in a dynamic and unpredictable global environment. The SDGs provide guidance for the implementation of sustainability in many areas of the social, economic and environmental activities of individuals, organisations and societies. The recent global health crisis, climate change and international geopolitical turmoil increase the importance of sustainability for societies and organisations and make it imperative to transform corporate business models towards sustainability. These developments are triggering changes in harmful socio-economic trends and in the determinants of global competitiveness of economies and businesses. The contributions in this Proceedings address the current economic and business challenges facing countries and businesses in the era of the new development paradigm, and cut across all fields of economics and business sciences.